High-superposition low-loss Fe-Si-Al metal soft magnetic powder and preparation method thereof

By adjusting the composition and particle size distribution of iron-silicon-aluminum powder and carbonyl iron powder, and by using an insulating coating layer, a high-overlapping, low-loss iron-silicon-aluminum metal soft magnetic powder was prepared. This solved the problem of high loss in existing iron-silicon-aluminum soft magnetic powder in high-frequency applications, and achieved high permeability and low loss.

CN121034793APending Publication Date: 2025-11-28德清鑫晨新材料有限公司
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202511566417.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-10-30
Publication Date
2025-11-28

AI Technical Summary

Technical Problem

Existing iron-silicon-aluminum soft magnetic powders suffer from high losses and reduced permeability in high-frequency applications, making it difficult to meet the requirements of high-power, highly integrated equipment. Furthermore, the large eddy current and hysteresis losses affect the efficiency and stability of the equipment.

Method used

By adjusting the composition and ratio of iron-silicon-aluminum powder and carbonyl iron powder, adding trace alloying elements such as Cr, Ni, Mo, Ti, and Co, controlling the particle size distribution, and using an insulating coating layer, high-addition-value and low-loss iron-silicon-aluminum metal soft magnetic powder is prepared. The process includes steps such as smelting, atomization, classification, annealing, mixing, and insulating coating.

Benefits of technology

It achieves high superposition performance and low loss under high frequency conditions, with an effective permeability of 95-112, DC superposition characteristics (H=100Oe) of 76%-81%, and power loss of 250-280mW/cm3 at 1MHz/100mT, thus improving the efficiency and stability of the equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121034793A_ABST
    Figure CN121034793A_ABST
Patent Text Reader

Abstract

The invention relates to high-superposition low-loss Fe-Si-Al metal soft magnetic powder and a preparation method thereof.The soft magnetic powder is composed of Fe-Si-Al powder and carbonyl iron powder, and the mass ratio of the Fe-Si-Al powder to the carbonyl iron powder is (6-8): (2-4); the Fe-Si-Al powder comprises, by mass, 6%-9% of Si, 4%-6% of Al, 0.5%-1.1% of Cr, 0.2%-1.5% of Ni, 0.6%-2.0% of Mo, 0.5%-0.8% of Ti, 1%-1.4% of Co and the balance Fe. The total content of Cr, Ni, Mo and Ti is 2.3-4.5%; the particle size of the carbonyl iron powder is 13-18 [mu] m. The soft magnetic material prepared from the high-superposition low-loss Fe-Si-Al metal soft magnetic powder can simultaneously give consideration to high superposition and low loss, the effective magnetic conductivity under 1MHz is 95-112, and the power loss under 1MHz / 100mT is 250-280mW / cm < 3 >.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of magnetic materials technology, specifically relating to high-addition, low-loss iron-silicon-aluminum metal soft magnetic powder and its preparation method. Background Technology

[0002] Soft magnetic materials are key fundamental materials in the electronics and information industry, playing an indispensable role in power conversion and signal processing. Iron-silicon-aluminum soft magnetic materials occupy an important position among many soft magnetic materials due to their high permeability, good high-frequency characteristics, and moderate cost.

[0003] However, existing iron-silicon-aluminum soft magnetic powders still have some shortcomings in practical applications. On the one hand, the superposition performance of some products is poor, and the permeability decreases significantly at high magnetic flux densities, making it difficult to meet the needs of high-power, highly integrated equipment. On the other hand, the loss problem is quite prominent, especially under high-frequency operating conditions, where eddy current losses and hysteresis losses are large, which not only reduces the efficiency of the equipment but may also cause severe overheating, affecting its service life and stability.

[0004] In existing technologies, researchers have tried various methods to improve the performance of iron-silicon-aluminum soft magnetic powder. For example, adjusting the alloy composition can optimize magnetic properties, but it is often difficult to achieve a balance between high superposition and low loss simultaneously. In terms of preparation processes, the control of powder particle size is not precise enough, resulting in uneven powder packing density and affecting the performance of magnetic properties. The insulation coating process is not perfect, resulting in poor insulation performance between powders and large eddy current losses. Therefore, developing an iron-silicon-aluminum soft magnetic powder with high superposition and low loss characteristics and its preparation method is of great practical significance. Summary of the Invention

[0005] This invention provides a high-superposition, low-loss iron-silicon-aluminum metal soft magnetic powder and its preparation method, addressing the problems of high loss and insufficient magnetic powder superposition performance in current high-frequency applications of iron-silicon-aluminum metal soft magnetic materials. The soft magnetic materials made from the high-superposition, low-loss iron-silicon-aluminum metal soft magnetic powder prepared by this invention can simultaneously achieve high superposition and low loss, with an effective permeability of 95–112 at 1MHz, a DC superposition characteristic (H=100Oe) of 76%–81%, and a power loss of 250–280 mW / cm² at 1MHz / 100mT. 3 .

[0006] In a first aspect, the present invention relates to a high-overlapping, low-loss iron-silicon-aluminum metal soft magnetic powder, which is composed of iron-silicon-aluminum powder and carbonyl iron powder, wherein the mass ratio of iron-silicon-aluminum powder to carbonyl iron powder is 6-8:2-4.

[0007] The iron-silicon-aluminum powder contains, by mass percentage, 6-9% Si, 4-6% Al, 0.5-1.1% Cr, 0.2-1.5% Ni, 0.6-2.0% Mo, 0.5-0.8% Ti, 1-1.4% Co, with the balance being Fe.

[0008] The total content of Cr, Ni, Mo and Ti elements is 2.3% to 4.5%.

[0009] The carbonyl iron powder contains, by mass percentage: N≤0.007%, O≤0.4%, C≤0.01%, with the balance being Fe.

[0010] The iron-silicon-aluminum powder has a particle size of 10–35 μm, and the mass ratio of particle sizes of 10–15 μm, 15–20 μm, and 20–35 μm is 1–2:3–4:2–3.

[0011] The carbonyl iron powder has a particle size of 13–18 μm.

[0012] The surfaces of the iron-silicon-aluminum powder and carbonyl iron powder are coated with an insulating coating layer with an average thickness of 5 nm to 12 nm.

[0013] Preferably, the mass ratio of the iron-silicon-aluminum powder to the carbonyl iron powder is 7-8:2-3.

[0014] Preferably, the total content of Cr, Ni, Mo and Ti elements in the iron-silicon-aluminum powder is 3 to 4%.

[0015] Preferably, the iron-silicon-aluminum powder has a particle size of 10–35 μm, and the mass ratio of particle sizes of 10–15 μm, 15–20 μm, and 20–35 μm is 2:4:3.

[0016] In a second aspect, the present invention relates to a method for preparing the high-overlapping low-loss iron-silicon-aluminum metal soft magnetic powder, the method comprising the following steps: (1) smelting and atomization steps: smelting raw materials conforming to the composition of the iron-silicon-aluminum powder under a protective atmosphere; atomizing the alloy melt by high-pressure gas atomization method, wherein the atomizing gas pressure is controlled at 6.0 MPa to 9.0 MPa, to obtain initial iron-silicon-aluminum powder.

[0017] (2) Grading step: The initial iron-silicon-aluminum powder is finely graded and screened using an air classifier to obtain iron-silicon-aluminum powder with a size of 10-35 μm.

[0018] (3) Powder pretreatment: The iron-silicon-aluminum powder is annealed at 500℃~700℃ in a hydrogen atmosphere for 1~4h.

[0019] (4) Mixing raw materials: Mix the iron-silicon-aluminum powder after annealing in step (3) with carbonyl iron powder in a certain proportion to obtain a mixed powder.

[0020] (5) Insulation coating: Passivating agent is added to the mixed powder after the above treatment for passivation treatment, and the mixture is dried. Sodium silicate additive is added to it and the mixture is continued to dry. Finally, binder is added to it and the mixture is dried to obtain the required high superposition low loss iron-silicon-aluminum metal soft magnetic powder.

[0021] Preferably, the passivating agent is phosphoric acid or boric acid; the binder is a mixture of 40 wt% polyethylene wax and 60 wt% silicone resin.

[0022] Preferably, the amount of passivating agent added is 0.1 to 1.1 wt% of the weight of the mixed powder, the amount of sodium silicate additive added is 0.3 to 1.2 wt% of the weight of the mixed powder, and the amount of binder added is 0.2 to 1.0 wt% of the weight of the mixed powder.

[0023] Preferably, the passivating agent and binder are dissolved in acetone or alcohol solvent before use, and the sodium silicate additive is dispersed in water before use.

[0024] Thirdly, the present invention relates to a high-overlapping low-loss iron-silicon-aluminum metal soft magnetic material, which uses the aforementioned high-overlapping low-loss iron-silicon-aluminum metal soft magnetic powder or the high-overlapping low-loss iron-silicon-aluminum metal soft magnetic powder prepared by the aforementioned high-overlapping low-loss iron-silicon-aluminum metal soft magnetic powder as raw material powder, presses the raw material powder into shape, and heat-treats it at 500℃~800℃ for 0.5~1h to obtain the high-overlapping low-loss iron-silicon-aluminum metal soft magnetic material.

[0025] The beneficial effects of this invention are as follows: By adjusting the iron-silicon-aluminum powder and carbonyl iron powder, and by adding a variety of trace alloying elements such as Cr, Ni, Mo, Ti, and Co to the iron-silicon-aluminum matrix powder, and strictly controlling their content range and mutual ratio, the synergistic regulatory effect of these elements on the electronic structure and lattice constant of the alloy can be utilized to simultaneously and precisely adjust the magnetocrystalline anisotropy constant K1 and the magnetostriction coefficient λs to a level close to zero, thereby reducing the coercivity and hysteresis loss of the material and significantly improving the permeability.

[0026] By combining 10-35μm iron-silicon-aluminum powder with 13-18μm carbonyl iron powder and designing a specific mass ratio for the iron-silicon-aluminum powder particle size distribution, extremely high packing and compression densities can be achieved, thereby improving saturation magnetic flux density and DC superposition capability. The mixed filling of iron-silicon-aluminum powder particles of different sizes and hydroxyl iron powder, combined with an insulating layer, effectively disrupts the macroscopic eddy current path, ensuring high superposition while keeping eddy current losses at an extremely low level.

[0027] It adopts a multi-layer composite coating structure of "passivation layer + inorganic insulation layer + organic binder". Precise thickness control of 5-12nm ensures a balance between insulation integrity, withstand voltage and low magnetic dilution effect, ensuring extremely low eddy current loss even at megahertz high frequencies.

[0028] The soft magnetic material made from the high-superposition, low-loss iron-silicon-aluminum metallic soft magnetic powder prepared by this invention exhibits excellent permeability, superposition performance, and low power loss. The effective permeability at 1MHz is 95–112, the DC superposition characteristic (H=100Oe) reaches 76%–81%, and the power loss at 1MHz / 100mT is 250–280 mW / cm. 3 This achieves high superposition performance and magnetic properties even under high frequency conditions. Attached Figure Description

[0029] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the embodiments will be briefly introduced below. It should be understood that the following drawings only show some embodiments of the present invention and should not be regarded as a limitation on the scope. For those skilled in the art, other related drawings can be obtained based on these drawings without creative effort.

[0030] Figure 1 This is a schematic diagram of the preparation method of high-superposition low-loss iron-silicon-aluminum metal soft magnetic powder disclosed in the embodiments of the present invention. Detailed Implementation

[0031] The technical solution of the present invention will now be clearly and completely described with reference to the accompanying drawings. Obviously, the described embodiments are only some, not all, of the embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0032] Existing iron-silicon-aluminum soft magnetic powders suffer from two main problems: firstly, their superposition performance is poor, and their permeability decreases significantly at high magnetic flux densities, making it difficult to meet the requirements of high-power, highly integrated devices; secondly, they exhibit significant losses, especially at high frequencies, with substantial eddy current and hysteresis losses. This not only reduces equipment efficiency but can also lead to severe overheating, affecting the equipment's lifespan and stability. Therefore, there is an urgent need to develop an iron-silicon-aluminum soft magnetic powder with high superposition and low loss characteristics.

[0033] To address the aforementioned technical problems, embodiments of the present invention provide a high-overlapping, low-loss iron-silicon-aluminum metal soft magnetic powder, which is composed of iron-silicon-aluminum powder and carbonyl iron powder, with a mass ratio of iron-silicon-aluminum powder to carbonyl iron powder of 6-8:2-4.

[0034] The iron-silicon-aluminum powder contains, by mass percentage, 6-9% Si, 4-6% Al, 0.5-1.1% Cr, 0.2-1.5% Ni, 0.6-2.0% Mo, 0.5-0.8% Ti, 1-1.4% Co, with the balance being Fe.

[0035] The total content of Cr, Ni, Mo and Ti elements is 2.3% to 4.5%.

[0036] The carbonyl iron powder contains, by mass percentage: N≤0.007%, O≤0.4%, C≤0.01%, with the balance being Fe.

[0037] The iron-silicon-aluminum powder has a particle size of 10–35 μm, and the mass ratio of particle sizes of 10–15 μm, 15–20 μm, and 20–35 μm is 1–2:3–4:2–3.

[0038] The carbonyl iron powder has a particle size of 13–18 μm.

[0039] The surfaces of the iron-silicon-aluminum powder and carbonyl iron powder are coated with an insulating coating layer with an average thickness of 5 nm to 12 nm.

[0040] In one embodiment, the mass ratio of the iron-silicon-aluminum powder to the carbonyl iron powder is 7-8:2-3.

[0041] In one embodiment, the total content of Cr, Ni, Mo, and Ti elements in the iron-silicon-aluminum powder is 3-4%.

[0042] In one embodiment, the iron-silicon-aluminum powder has a particle size of 10–35 μm, and the mass ratio of particle sizes of 10–15 μm, 15–20 μm, and 20–35 μm is 2:4:3.

[0043] Iron-silicon-aluminum powder possesses high magnetic permeability and low hysteresis loss, but its superposition performance is somewhat limited. Carbonyl iron powder, with its high density and good formability, can effectively improve the superposition performance of magnetic powders. When the mass ratio of iron-silicon-aluminum powder to carbonyl iron powder is in the range of 6–8:2–4 (preferably 7–8:2–3), the advantages of the two powders can be complemented. Iron-silicon-aluminum powder, as the main component, is mostly irregular or nearly spherical in shape, resulting in numerous irregular voids when the particles naturally accumulate. Carbonyl iron powder typically exhibits a highly spherical, fine-particle-size onion-like lamellar structure, possessing excellent flowability and filling properties, and extremely high saturation magnetization. By filling a 6–8 part iron-silicon-aluminum powder skeleton with carbonyl iron powder of 13–18 μm at a mass ratio of 2–4 parts, the fine carbonyl iron spherical particles can efficiently fill the voids formed by the larger iron-silicon-aluminum particles. This composite process significantly improves the tap density and loose packing density of the mixed powder. In subsequent pressing and molding, a higher initial density means that the target density can be achieved with lower pressure, or a higher density can be obtained under the same pressure, thereby directly improving the effective permeability and saturation magnetic induction, which is key to improving DC superposition performance. If the proportion of carbonyl iron powder is too low, the filling effect is not obvious; if the proportion is too high, although Bs will continue to increase, the performance of the entire system will be biased towards the characteristics of carbonyl iron powder, that is, the resistivity decreases and the high-frequency loss increases, thus losing the low-loss advantage of iron-silicon-aluminum. A further preferred ratio is 7-8:2-3, which can achieve a more ideal balance between the two properties.

[0044] The iron-silicon-aluminum powder contains, by mass percentage, 6-9% Si, 4-6% Al, 0.5-1.1% Cr, 0.2-1.5% Ni, 0.6-2.0% Mo, 0.5-0.8% Ti, 1-1.4% Co, with the balance being Fe.

[0045] Si element: The addition of Si can improve the resistivity of iron-silicon-aluminum powder and reduce eddy current loss. A content range of 6 to 9% can ensure the improvement of resistivity while avoiding the increase of material brittleness due to excessive Si content, which would affect the processing performance.

[0046] Al element: Al can improve the magnetic stability and corrosion resistance of materials. A content of 4-6% can work synergistically with Si to optimize the magnetocrystalline anisotropy constant K1 and magnetostriction coefficient λs, making them closer to zero, thereby increasing the initial permeability and reducing coercivity.

[0047] Cr and Mo are potent resistivity-enhancing elements. Dissolved in the Fe matrix, they increase the scattering of conduction electrons, significantly improving the resistivity of the alloy itself. This is crucial for reducing eddy current losses within the particles. Furthermore, the addition of Cr and Mo helps improve the material's corrosion resistance and high-temperature stability. An addition of 0.5–1.1% Cr effectively enhances the stability of soft magnetic powder under various environments with minimal negative impact on magnetic properties. An addition of 0.6–2.0% Mo further helps reduce losses and enhances the material's stability under high-temperature operating conditions.

[0048] Ni element: Ni can improve the toughness and processing performance of materials. A content of 0.2% to 1.5% can improve the formability of powder, which is convenient for subsequent pressing and forming processes. Ti element: Ti can refine grains. Small grains are beneficial to reduce hysteresis loss and improve the magnetic permeability and magnetic stability of materials. A content of 0.5% to 0.8% can effectively play its role. Excessive content may introduce impurity phases and affect magnetic properties.

[0049] Co element: Co can adjust the magnetocrystalline anisotropy of materials. An addition of 1 to 1.4% can combine with other elements to make K1 and λs closer to zero, thereby improving magnetic properties. The total content of Cr, Ni, Mo, and Ti is 2.3%–4.5%. These four elements have a comprehensive impact on the resistivity, thermal stability, and processing performance of the material. The limit on the total content reflects the comprehensive balance of all the above trace elements. If the total content is too low, it is difficult to achieve the effect of optimizing performance; if the total content is too high, it may lead to an overly complex alloy composition, introducing too many non-magnetic phases, reducing magnetic permeability, and increasing losses. A further preferred content is 3%–4%, which allows the effects of each element to be more fully and synergistically exerted.

[0050] Carbonyl iron powder contains N≤0.007%, O≤0.4%, C≤0.01% by mass, with the balance being Fe. The content of N, O, and C must be strictly controlled, as these impurities can adversely affect magnetic properties.

[0051] The iron-silicon-aluminum powder has a particle size of 10–35 μm, with a mass ratio of 10–15 μm, 15–20 μm, and 20–35 μm particles of 1–2:3–4:2–3. The carbonyl iron powder has a particle size of 13–18 μm. This particle size range and ratio design can improve the packing density of the powder. Small-diameter powder can fill the gaps between large-diameter powders. The small particle group (10–15 μm) together with the carbonyl iron powder (13–18 μm) of similar size acts as a fine filler, filling the even smaller gaps remaining after the medium and large-diameter powders have filled. This makes the magnetic powder structure more compact after molding, which is beneficial to the transmission of magnetic flux, thereby improving the superposition performance. At the same time, a reasonable particle size distribution can reduce eddy current losses because finer powder particles can shorten the eddy current path. A further optimized mass ratio of 2:4:3 can achieve an even better packing density. This is one of the key physical mechanisms by which this invention can simultaneously achieve "high superposition" and "low loss".

[0052] The surfaces of iron-silicon-aluminum powder and carbonyl iron powder are coated with an insulating layer with an average thickness of 5 nm to 12 nm. This insulating layer effectively isolates powder particles and reduces eddy current losses between them. If the layer is too thin, the insulation effect is poor; if it is too thick, it increases the gaps between powder particles, reduces the packing density, and makes the volume fraction of the non-magnetic phase non-negligible. This severely "dilutes" the magnetism, leading to a significant decrease in the effective permeability and saturation flux density of the magnetic powder core, thus impairing the material's magnetic properties and affecting permeability. A thickness range of 5 nm to 12 nm strikes a balance between insulation performance and magnetic properties.

[0053] like Figure 1 As shown, the preparation method of the high superposition low loss iron-silicon-aluminum metal soft magnetic powder of the present invention includes the following steps: (1) smelting and atomization step: smelting raw materials that conform to the composition of the iron-silicon-aluminum powder under a protective atmosphere; atomizing the alloy melt by high pressure gas atomization method, wherein the atomizing gas pressure is controlled at 6.0MPa to 9.0MPa, to obtain initial iron-silicon-aluminum powder.

[0054] (2) Grading step: The initial iron-silicon-aluminum powder is finely graded and screened using an air classifier to obtain iron-silicon-aluminum powder with a size of 10-35 μm.

[0055] (3) Powder pretreatment: The iron-silicon-aluminum powder is annealed at 500℃~700℃ in a hydrogen atmosphere for 1~4h.

[0056] (4) Mixing raw materials: Mix the iron-silicon-aluminum powder after annealing in step (3) with carbonyl iron powder in a certain proportion to obtain a mixed powder.

[0057] (5) Insulation coating: Passivating agent is added to the mixed powder after the above treatment for passivation treatment, and the mixture is dried. Sodium silicate additive is added to it and the mixture is continued to dry. Finally, binder is added to it and the mixture is dried to obtain the required high superposition low loss iron-silicon-aluminum metal soft magnetic powder.

[0058] In one embodiment, the passivating agent is phosphoric acid or boric acid; the binder is a mixture of 40 wt% polyethylene wax and 60 wt% silicone resin.

[0059] In one embodiment, the amount of passivating agent added is 0.1 to 1.1 wt% of the weight of the mixed powder, the amount of sodium silicate additive added is 0.3 to 1.2 wt% of the weight of the mixed powder, and the amount of binder added is 0.2 to 1.0 wt% of the weight of the mixed powder.

[0060] In one embodiment, the passivating agent and binder are dissolved in acetone or alcohol solvent before use, and the sodium silicate additive is dispersed in water before use.

[0061] In the melting and atomization steps, the alloy melt is atomized using a high-pressure gas atomization method, with the atomizing gas pressure controlled between 6.0 MPa and 9.0 MPa. This pressure range ensures that the alloy melt is fully broken into fine droplets, forming a powder with uniform particle size and good sphericity after cooling.

[0062] In the classification step, an air classifier is used to finely classify the initial iron-silicon-aluminum powder, screening out iron-silicon-aluminum powder with a particle size of 10–35 μm. The air classifier is characterized by high classification accuracy, which can precisely control the powder particle size and ensure that the particle size range meets the design requirements is obtained.

[0063] Powder pretreatment involves annealing iron-silicon-aluminum powder at 500℃–700℃ in a hydrogen atmosphere for 1–4 hours. The reducing properties of hydrogen remove oxide films and adsorbed impurities from the powder surface, improving powder purity. Annealing at 500℃–700℃ is crucial; below 500℃, atomic diffusion is insufficient, leading to inadequate stress relief, while above 700℃, negative effects may occur. Firstly, grains may grow rapidly beyond their optimal size range, increasing hysteresis loss. Secondly, slight sintering adhesion between particles may occur, compromising the powder's individuality. Excessively high temperatures may also induce unfavorable magnetic transformations in certain metastable phases within the alloy. For example, in compositions containing Cr, Ni, Mo, and Ti, hard and brittle second phases may precipitate at grain boundaries within this temperature range. These second phases become strong pinning centers for domain wall movement, resulting in a sharp increase in coercivity and deterioration of losses. Therefore, strictly controlling the temperature within this range allows for sufficient stress relief while minimizing these unfavorable microstructural evolutions. Annealing time of 1 to 4 hours can ensure that internal stress is fully released and impurities are fully removed.

[0064] For insulating coating, a passivating agent, such as phosphoric acid or boric acid, is added to the mixed powder for passivation treatment at a rate of 0.1–1.1 wt% of the powder weight. Phosphoric acid or boric acid reacts with the metal surface to form an extremely dense and chemically stable phosphate or borate passivation film, enhancing insulation performance and improving the chemical stability of the powder. Insufficient addition results in poor passivation; excessive addition may affect the magnetic properties of the powder.

[0065] The amount of sodium silicate additive added is 0.3–1.2 wt% of the weight of the mixed powder. The aqueous dispersion of sodium silicate is mixed with the powder, and the water is evaporated by controlling the temperature and stirring. The sodium silicate will then be uniformly deposited on the surface of the passivated particles. Sodium silicate can further enhance the strength and stability of the insulating coating and improve the corrosion resistance of the powder.

[0066] The binder is a mixture of 40 wt% polyethylene wax and 60 wt% silicone resin, added at a rate of 0.2–1.0 wt% of the magnetic powder weight. Polyethylene wax is an excellent lubricant; during pressing, it effectively reduces friction between particles and between particles and the mold wall, resulting in more uniform pressure transmission and a more uniform density distribution in the final magnetic core, preventing density gradients and cracking. Silicone resin is a high-performance polymer that further cross-links and cures during heat treatment, forming a three-dimensional network structure that acts as a bond and reinforcement. It fills any micropores or cracks that may exist in the sodium silicate layer, forming an "inorganic-organic" composite structure, further improving insulation reliability. Simultaneously, the cured silicone resin also imparts better mechanical strength to the magnetic core.

[0067] This invention discloses a high-overlapping, low-loss iron-silicon-aluminum metal soft magnetic material, which uses the aforementioned high-overlapping, low-loss iron-silicon-aluminum metal soft magnetic powder or the high-overlapping, low-loss iron-silicon-aluminum metal soft magnetic powder prepared by the aforementioned method as raw material powder. The raw material powder is pressed into shape and then heat-treated at 500℃~800℃ for 0.5~1h to obtain the high-overlapping, low-loss iron-silicon-aluminum metal soft magnetic material.

[0068] Using the aforementioned high-overlapping, low-loss iron-silicon-aluminum metal soft magnetic powder as raw material, the powder is pressed into shape and then heat-treated at 500℃~800℃ for 0.5~1h to obtain a high-overlapping, low-loss iron-silicon-aluminum metal soft magnetic material. Pressing allows the magnetic powder to form a dense, integral structure, and the heat treatment temperature of 500℃~800℃ eliminates the internal stress generated during pressing, promotes the curing of the binder and the stability of the insulating coating layer, and improves the magnetic and mechanical properties of the soft magnetic material.

[0069] The embodiments of the present invention are described in detail below. The high-overlapping, low-loss iron-silicon-aluminum metal soft magnetic powder used in the embodiments is as follows: The soft magnetic powder is composed of iron-silicon-aluminum powder and carbonyl iron powder, and the mass ratio of iron-silicon-aluminum powder to carbonyl iron powder is 6-8:2-4; the iron-silicon-aluminum powder contains, by mass percentage, 6-9% Si, 4-6% Al, 0.5-1.1% Cr, 0.2-1.5% Ni, 0.6-2.0% Mo, 0.5-0.8% Ti, 1-1.4% Co, and the balance is Fe.

[0070] The total content of Cr, Ni, Mo and Ti elements is 2.3% to 4.5%.

[0071] The carbonyl iron powder contains, by mass percentage: N≤0.007%, O≤0.4%, C≤0.01%, with the balance being Fe.

[0072] The iron-silicon-aluminum powder has a particle size of 10–35 μm, and the mass ratio of particle sizes of 10–15 μm, 15–20 μm, and 20–35 μm is 1–2:3–4:2–3.

[0073] The carbonyl iron powder has a particle size of 13–18 μm.

[0074] The surfaces of the iron-silicon-aluminum powder and carbonyl iron powder are coated with an insulating coating layer with an average thickness of 5 nm to 12 nm.

[0075] The preparation method of the high superposition low loss iron-silicon-aluminum metal soft magnetic powder used in the embodiment includes the following steps: (1) Melting and atomization steps: the raw materials that conform to the composition of the iron-silicon-aluminum powder are melted under a protective atmosphere; the alloy melt is atomized by high pressure gas atomization method, wherein the atomizing gas pressure is controlled at 6.0MPa to 9.0MPa to obtain the initial iron-silicon-aluminum powder.

[0076] (2) Grading step: The initial iron-silicon-aluminum powder is finely graded and screened using an air classifier to obtain iron-silicon-aluminum powder with a size of 10-35 μm.

[0077] (3) Powder pretreatment: The iron-silicon-aluminum powder is annealed at 500℃~700℃ in a hydrogen atmosphere for 1~4h.

[0078] (4) Mixing raw materials: Mix the iron-silicon-aluminum powder after annealing in step (3) with carbonyl iron powder in a certain proportion to obtain a mixed powder.

[0079] (5) Insulation coating: Passivating agent is added to the mixed powder after the above treatment for passivation treatment, and the mixture is dried. Sodium silicate additive is added to it and the mixture is continued to dry. Finally, binder is added to it and the mixture is dried to obtain the required high superposition low loss iron-silicon-aluminum metal soft magnetic powder.

[0080] The passivating agent is phosphoric acid or boric acid; the binder is a mixture of 40 wt% polyethylene wax and 60 wt% silicone resin.

[0081] The amount of passivating agent added is 0.1 to 1.1 wt% of the weight of the mixed powder, the amount of sodium silicate additive added is 0.3 to 1.2 wt% of the weight of the mixed powder, and the amount of binder added is 0.2 to 1.0 wt% of the weight of the mixed powder.

[0082] The passivating agent and binder are dissolved in acetone or alcohol before use, and the sodium silicate additive is dispersed in water before use.

[0083] The high-overlapping low-loss iron-silicon-aluminum metal soft magnetic material used in this embodiment is obtained by using the aforementioned high-overlapping low-loss iron-silicon-aluminum metal soft magnetic powder or the high-overlapping low-loss iron-silicon-aluminum metal soft magnetic powder prepared by the aforementioned method as raw material powder. The raw material powder is pressed into shape and then heat-treated at 500℃~800℃ for 0.5~1h to obtain the high-overlapping low-loss iron-silicon-aluminum metal soft magnetic material.

[0084] The composition of the high-superposition low-loss iron-silicon-aluminum metal soft magnetic powder in Examples 1-4 and Comparative Examples 1-4 of the present invention is shown in Table 1.

[0085] Table 1: Composition of iron-nickel alloy powders in Examples 1-4 and Comparative Examples 1-4:

[0086] The process parameters used in the preparation methods of Examples 1-4 and Comparative Examples 5-7 of this invention are shown in Table 2.

[0087] Table 2: Process parameters used in the preparation methods of Examples 1-4 and Comparative Examples 5-7:

[0088] The preparation process parameters for Comparative Examples 1 to 4 are the same as those for Example 1, as detailed in Table 1.

[0089] The compositions of the high-overlapping low-loss iron-silicon-aluminum metal soft magnetic powders in Comparative Examples 5-7 are the same as those in Example 2, and the preparation process parameters are shown in Table 2.

[0090] The high-superposition low-loss iron-silicon-aluminum metal soft magnetic materials prepared in the above-mentioned examples and comparative examples were measured for their effective permeability, DC superposition characteristics (H=100Oe), and power loss (1MHz, 100mT) at 1MHz. The results are shown in Table 3.

[0091] Table 3: Performance data of the examples and comparative examples:

[0092] Table 3 shows that the soft magnetic material made from the high-superposition, low-loss iron-silicon-aluminum metal soft magnetic powder prepared in this invention has excellent permeability, superposition performance, and low power loss. The effective permeability at 1MHz is 95–112, the DC superposition characteristic (H=100Oe) can reach 76%–81%, and the power loss at 1MHz / 100mT is 250–280mW / cm. 3 .

[0093] Compared to Example 1, Comparative Examples 1 to 4, after adjusting the composition of the iron-silicon-aluminum powder, the particle size distribution of the magnetic powder, and the thickness of the coating layer of the high-superposition low-loss iron-silicon-aluminum metal soft magnetic powder, resulted in insufficient compactness or insulation of the magnetic powder, weakened the synergistic effect of magnetic properties, significantly reduced magnetic permeability and DC superposition characteristics, and increased power loss.

[0094] Compared to Example 2, Comparative Examples 5-7 adjusted the annealing temperature, passivator addition amount, sodium silicate addition amount, and binder addition amount in preparing the iron-nickel alloy powder, and adjusted the heat treatment temperature in preparing the soft magnetic material. As a result, an effective coating layer could not be formed, stress relief could not be achieved, the magnetic permeability decreased significantly, the DC superposition characteristics decreased significantly, and the power loss increased.

[0095] The technical features of the above embodiments can be combined in any way. For the sake of brevity, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

Claims

1. A high-cumulative, low-loss iron-silicon-aluminum metal soft magnetic powder, characterized in that, The soft magnetic powder is composed of iron-silicon-aluminum powder and carbonyl iron powder, with a mass ratio of 6-8:2-4. The iron-silicon-aluminum powder contains, by mass percentage: Si 6-9%, Al 4-6%, Cr 0.5-1.1%, Ni 0.2-1.5%, Mo 0.6-2.0%, Ti 0.5-0.8%, and Co. The carbonyl iron powder contains 1-1.4% N, with the balance being Fe; and the total content of Cr, Ni, Mo, and Ti elements is 2.3-4.5%. The carbonyl iron powder contains, by mass percentage: N≤0.007%, O≤0.4%, C≤0.01%, with the balance being Fe. The iron-silicon-aluminum powder has a particle size of 10-35 μm, and the mass ratio of particle sizes of 10-15 μm, 15-20 μm, and 20-35 μm is 1-2:3-4:2-3. The carbonyl iron powder has a particle size of 13-18 μm. The iron-silicon-aluminum powder and the carbonyl iron powder are coated with an insulating coating layer with an average thickness of 5 nm to 12 nm.

2. The high-cumulative, low-loss iron-silicon-aluminum metal soft magnetic powder according to claim 1, characterized in that, The mass ratio of the iron-silicon-aluminum powder to the carbonyl iron powder is 7-8:2-3.

3. The high-cumulative, low-loss iron-silicon-aluminum metal soft magnetic powder according to claim 1, characterized in that, The total content of Cr, Ni, Mo and Ti elements in the iron-silicon-aluminum powder is 3 to 4%.

4. The high-cumulative, low-loss iron-silicon-aluminum metal soft magnetic powder according to claim 1, characterized in that, The iron-silicon-aluminum powder has a particle size of 10–35 μm, and the mass ratio of particle sizes of 10–15 μm, 15–20 μm, and 20–35 μm is 2:4:

3.

5. The method for preparing high-cumulative, low-loss iron-silicon-aluminum metal soft magnetic powder according to any one of claims 1 to 4, characterized in that, The method includes the following steps: (1) Melting and atomization step: the raw materials that conform to the composition of the iron-silicon-aluminum powder are melted under a protective atmosphere; the alloy melt is atomized by high-pressure gas atomization method, wherein the atomizing gas pressure is controlled at 6.0MPa to 9.0MPa to obtain initial iron-silicon-aluminum powder; (2) Grading step: the initial iron-silicon-aluminum powder is finely graded and screened to obtain iron-silicon-aluminum powder of 10 to 35μm using an air classifier; (3) Powder pretreatment: the iron-silicon-aluminum powder is annealed at 500℃ to 700℃ under a hydrogen atmosphere for 1 to 4 hours; (4) Mixing raw materials: the iron-silicon-aluminum powder after annealing in step (3) is mixed with carbonyl iron powder in proportion to obtain mixed powder; (5) Insulation coating: the mixed powder after the above treatment is added to a passivating agent for passivation treatment, dried after mixing, sodium silicate additive is added to it, and mixing is continued until dry. Finally, a binder is added to it, and after mixing and drying, the desired high-overlapping low-loss iron-silicon-aluminum metal soft magnetic powder is obtained.

6. The method for preparing high-cumulative, low-loss iron-silicon-aluminum metal soft magnetic powder according to claim 5, characterized in that, The passivating agent is phosphoric acid or boric acid; the binder is a mixture of 40 wt% polyethylene wax and 60 wt% silicone resin.

7. The method for preparing high-cumulative, low-loss iron-silicon-aluminum metal soft magnetic powder according to claim 6, characterized in that, The amount of passivating agent added is 0.1 to 1.1 wt% of the weight of the mixed powder, the amount of sodium silicate additive added is 0.3 to 1.2 wt% of the weight of the mixed powder, and the amount of binder added is 0.2 to 1.0 wt% of the weight of the mixed powder.

8. The method for preparing high-cumulative, low-loss iron-silicon-aluminum metal soft magnetic powder according to claim 5, characterized in that, The passivating agent and binder are dissolved in acetone or alcohol before use, and the sodium silicate additive is dispersed in water before use.

9. A high-superposition, low-loss iron-silicon-aluminum metal soft magnetic material, characterized in that, Using the high-overlapping low-loss iron-silicon-aluminum metal soft magnetic powder of any one of claims 1 to 4 or the high-overlapping low-loss iron-silicon-aluminum metal soft magnetic powder prepared by any one of claims 5 to 8 as raw material powder, the raw material powder is pressed into shape and heat-treated at 500℃ to 800℃ for 0.5 to 1 h to obtain high-overlapping low-loss iron-silicon-aluminum metal soft magnetic material.

Citation Information

Cited By

  • High-frequency ultralow-loss iron-nickel alloy powder and preparation process thereof

    CN121571645A